Revision of Ganomymar De Santis, 1972, a remarkable genus of Mymaridae (Hymenoptera, Chalcidoidea) from Madagascar - Triapitsyn, Serguei V. (European Journal of Taxonomy, 2021)
A rare fairyfly (Hymenoptera, Mymaridae) genus, Ganomymar De Santis, 1972, is revised and rediagnosed based on both sexes; its males were previously unknown. This genus, which has remarkable structures on the propodeum and peculiar fore wings in females, is known only from Madagascar in the Afrotropical region. Its type species, Ganomymar dessarti De Santis, 1972, is redescribed and illustrated based on a non-type female specimen. Three new species of Ganomymar are described: G. caslot sp. nov., G. libertatium sp. nov., and G. zuparkoi sp. nov. The species are placed in two distinct species groups. A key to females of the four species is provided.